(untitled) (The Research of Medical Science Review, 2025)
This study examines the impact of various training methods on performance metrics, injury risks, and their interrelationships among athletes. A total of 100 participants, divided equally across four training groups (Strength Training, Balance/Stability Training, Plyometric Training, and Sport-Specific Drills), were assessed for injury risk levels (low, moderate, high) and performance outcomes, including Y-Balance Score, Force Plate Stability, Single-Leg Stance Duration, and FMS Score. Statistical analyses, including One-Way ANOVA, Chi-Square tests, and correlation analysis, were conducted to evaluate differences, associations, and interrelationships among the variables. The One-Way ANOVA revealed significant differences between training groups (p = 0.02), indicating that training types influence performance and injury outcomes. The Chi- Square analysis (p = 0.026) demonstrated a significant association between training methods and injury risks, with Plyometric Training participants exhibiting higher injury risks, whereas Strength and Balance/Stability Training groups were linked to lower risks. Correlation analysis showed a strong positive relationship between Y-Balance Score and FMS Score (r = 0.65), highlighting the connection between balance and functional movement. Conversely, Force Plate Stability demonstrated negative correlations with performance measures, suggesting a potential trade-off between static stability and dynamic performance. The findings align with previous studies emphasizing the efficacy of Strength and Balance/Stability Training in reducing injury risks and enhancing functional outcomes, while highlighting the injury risks associated with Plyometric Training. This study underscores the need for tailored, sport-specific training programs to optimize performance and minimize injury risks, contributing to the growing body of evidence in athletic training and injury prevention.